2017
DOI: 10.1021/jacs.7b00452
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cu Atoms in Pd Lattice: Forming Highly Selective Sites for Photocatalytic Conversion of CO2 to CH4

Abstract: Photocatalytic conversion of CO to CH, a carbon-neutral fuel, represents an appealing approach to remedy the current energy and environmental crisis; however, it suffers from the large production of CO and H by side reactions. The design of catalytic sites for CO adsorption and activation holds the key to address this grand challenge. In this Article, we develop highly selective sites for photocatalytic conversion of CO to CH by isolating Cu atoms in Pd lattice. According to our synchrotron-radiation character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
362
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 503 publications
(370 citation statements)
references
References 37 publications
7
362
0
1
Order By: Relevance
“…Pt/Cu alloy NPs on TiO 2 mesoporous hollow sphere have been applied in CO 2 reduction for the preferential syngas production . CH 4 was also selectively produced over Pd/Cu bimetallic NPs on TiO 2 . Once again, the content of the two metals in the NPs controlled activity and selectivity.…”
Section: Cu‐based Materials For Co2 Photocatalytic Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt/Cu alloy NPs on TiO 2 mesoporous hollow sphere have been applied in CO 2 reduction for the preferential syngas production . CH 4 was also selectively produced over Pd/Cu bimetallic NPs on TiO 2 . Once again, the content of the two metals in the NPs controlled activity and selectivity.…”
Section: Cu‐based Materials For Co2 Photocatalytic Reductionmentioning
confidence: 99%
“…The molar ratio of the two metals controlled the energy level of the Cu d ‐band center estimated by theoretical DFT calculations. When Cu atoms are surrounded by more Pd atoms, the electronic structure is affected mostly by the Pd atoms and the d ‐band center of each Cu site is elevated increasing the catalytic activity …”
Section: Cu‐based Materials For Co2 Photocatalytic Reductionmentioning
confidence: 99%
“…Notably, Cu can yield rich hydrocarbon products from CO 2 reduction, such as methanol and methane, which have received giant attention for both photocatalytic and electrocatalytic processes [120][121][122]. In terms of PEC CO 2 reduction, one should also consider those matters to improve the Faradaic efficiency and suppress the competitive reactions when employing metals as co-catalysts.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…Here we name two candidates for this requirement which may boost the development in the future. One is Cu-based catalysts [114,121,122]. Many studies have revealed that Cu-based catalysts can yield deep-reduced products with high selectivity.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…For instance, Zeng et al modified ultrathin SnS 2 nanosheets by nickel doping, achieving a high formate FE of 80% with a current density of 19.6 mA cm −2 at −0.9 V versus reversible hydrogen electrode (RHE), and the improved activity is attributed to the defect level and reduced work function generated by nickel doping . For another example, doping Cu atoms into the Pd lattice can raise the d‐band of center of Cu atoms, thus promoting CO 2 activation and conversion to methane …”
Section: Introductionmentioning
confidence: 99%